Root endophytic Phialocephala fortinii and Talaromyces verruculosus enhance growth and affect heavy metal tolerance of Miscanthus sinensis Andersson growing naturally at a mine site - Xingyan Lu; Keiko Yamaji; Toshikatsu Haruma; Kohei Doyama; Hayato Masuya (Journal of Plant Interactions)
Miscanthus sinensis Andersson naturally grows at mining sites and accumulates heavy metals, suggesting heavy metal tolerance. This study aimed to elucidate the heavy metal tolerance mechanisms of M. sinensis, which naturally grew at a mine site, considering root endophytes. Elemental analysis by inductively coupled plasma-optical emission spectroscopy showed that M. sinensis highly accumulated zinc and lead in adventitious roots and dead root bark, exhibiting tolerance via these elemental removals in dead root bark. Phenolic analysis by high-performance liquid chromatography revealed chlorogenic acid production in adventitious roots. Phialocephala fortinii, which showed the highest appearance, and Talaromyces verruculosus, which produced gluconic acid as a zinc detoxicant, were isolated from adventitious roots of M. sinensis. In inoculation tests, P. fortinii and T. verruculosus significantly enhanced seedling growth by increasing potassium uptake and possibly indole-3-acetic acid production. Our results provide fundamental knowledge for using M. sinensis and root endophytes for revegetation at mining sites.